The effect of treating generalized anxiety disorder on psychoactive substance abuse and dependency in Erbil city - Tahir, Diyar Hussein; Albarazanjy, Baran Kamal; Ali, Sirwan Kamil (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Generalized anxiety disorder is a common psychiatric disorder; it may act as a risk factor for psychoactive substance abuse and dependency development. The objectives are to assess the degree of abuse and dependency in generalized anxiety disorder patients, and the effect of treating the disorder on substances abuse and dependency. Methods: 120 patients with generalized anxiety disorder, diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), were studied from January 2007 to June 2008 for the presence of psychoactive substance abuse and dependency according to DSM-IV. All cases were managed for six months by the tricyclic antidepressant imipramine (35-75mg/day), with counseling to decrease anxiety by reassurance and anxiety management including relaxation training, in addition to supporting and encouraging the patients with abuse to stop the used psychoactive substances by a tapering schedule over weeks. Results: Substance abuse were presents in 32.5% of patients (tobacco 17.5%, benzodiazepines 13.3%, and alcohol 1.7%), this rate decreased to 13.3% (tobacco 11.7%, benzodiazepines 0.8%, and alcohol 0.8%) six months after starting treatment. The decrease in benzodiazepines abuse and dependency was greater than that in tobacco or alcohol. Conclusion: Generalized anxiety disorder appears to encourage abuse on psychoactive substances. Treating the disorder decreases abuse and using imipramine appears to have a good therapeutic effect on generalized anxiety disorder with low risk for abuse.